The relationship between personality and the oral fluency of students on the second semester of 2012 at the Foreign Languages Department in the University of El Salvador - Mancía Fuentes, Elda Melissa
The purpose of this study was to find the possible relation between personality and oral fluency of the students from the Foreign Language Department of the University of El Salvador. It is believed that fluency is difficult to develop for different affecting factors that may interfere or stop students from being fluent. Among those affecting factors personality has a great significance. A quantitative methodology was utilised in this study. The quantitative research data consisted of an oral interview with 32 participants analysing the interviews with a rubric and getting a score to label students in a specific level of fluency. The second instrument was a questionnaire personality test that the same 32 students answered so the researchers could identify the personality type based on a score. The results of the fluency interview revealed an unexpected result by finding introverts better positioned. Another unexpected result was that the majority of the sample was classified as ambivert in the personality test leaving just a small sample to compare complete extroverts with introverts. The researchers recommend for future research a correlational study with fluency and other sorts of affecting factor other than personality since it has been concluded that personality is not the only one that will determine the level of fluency a student may achieve.